Can regenerative agriculture restore soil health and bridge gender gap in farm productivity? Empirical insights from Nigeria - Daudu, Abdulrazaq Kamal; Kareem, Oyedola Waheed; Olatinwo, Latifat Kehinde; Mariam B. Alwajud-Adewusi; Egbewole, Halimah Olayinka (Dynamics of Rural Society Journal, 2025)
This study investigates the potential of Regenerative Agriculture (RA) to improve soil health and address gender disparities in agricultural productivity among smallholder farmers in Nigeria. Using data from a randomized controlled trial, the research evaluates gender-specific RA adoption rates and their impact on farm productivity through Blinder-Oaxaca decomposition and Propensity Score Matching (PSM). Results reveal significant adoption disparities, with male farmers benefitting from larger farms, better education, and higher incomes compared to female farmers. RA adoption improved yields for both genders, though productivity gaps persisted due to structural barriers, including limited access to land, credit, and extension services for women. Female farmers, despite adopting RA practices, often faced greater challenges in maximizing productivity due to socio-economic constraints. These findings underscore the importance of addressing resource inequities and promoting gender-sensitive interventions to encourage equitable adoption of RA. Enhancing women’s access to agricultural education, financial support, and climate-related information is essential. Additionally, fostering community-based platforms and collaboration can further strengthen sustainable practices. This study provides critical insights for policymakers and practitioners to improve smallholder farmers’ productivity, promote sustainable agriculture, and build climate-resilient food systems in Nigeria and similar regions facing comparable challenges.